PENGARUH PRODUK HARGA DAN BIAYA PROMOSI TERHADAP TINGKAT KUNJUNGAN DI COUNTER HANDPHONE DI KECAMATAN KEDIRI KABUPATEN TABANAN - NI L PT BUDIARI; I MADE HARY KUSMAWAN; SILUH KOMANG AMRITHA DAARA (GANEC SWARA, 2023)
The problems in this study are: 1) Does the product partially have a significant effect on the level of visits at Mobile Counters in Kediri District, Tananan Regency. 2) Is the price partially significant effect on the level of visits at the Mobile Counter in Kediri District, Tananan Regency. 3). Does the promotion cost have a partial effect on the level of visits at the Mobile Counter in Kediri District, Tananan Regency. 4) Do products, promotional costs, and prices have a significant effect simultaneously on the level of visits at Mobile Counters in Kediri sub-district, Tananan Regency. The purpose of this study was to determine: The effect of product, promotional costs and prices partially or simultaneously on the level of visits at Mobile Counters in Kediri sub-district, Tananan Regency. The data analysis technique used to determine the effect of the independent variables on the dependent variable is multiple linear regression analysisBased on data analysis, it can be concluded as follows: 1) The product has a positive and significant effect partially on the level of visits at mobile counters in the District of Kediri. 2) Price has a positive and partially significant effect on the level of visits at Mobile Counters in Kediri District. 3) Promotional costs have a positive and partially significant effect on the level of visits at Mobile Counters in Kediri District. 4) Products, promotional costs, and prices have a positive and significant effect simultaneously on the level of visits at Mobile Counters in the Kediri sub-district.